Libertate, necesitate și raționalitate în comportamentul de consum al populației - Preotesi, Mihnea (Calitatea Vieții, 2007)
The collapse of the communist regime led to an “explosion” of population’s expectations regarding the capacity to satisfy some of the needs that they were aware of and were not satisfied during the latest years of the communist regime. The first months of the post-communist period represented for the majority of the Romanian population a period of “abundance” of goods that were accesible, comparing to the previous period. The “postrevolutionary” enthusiasm, maintained by generous social measures “with reparatory purpose” (C. Zamfir, 1999), was stopped in a rather brutal manner by the social effects of the economic transition, felt by the majority of population in the drastical diminution of the capacity of purchasing, correlated with a process of legitimation of a large set of needs, in accordance with those characteistics to the assumed model of the capitalist welfare states. The perspective on the consumption behavior, suggested by the present study, will be a partial one, focused on a certain part of population, representing, in fact, the majoritory of population whose consumption behavior is under the severe conditioning of the economic compulsions of the transition and for whom the freedom of option in this area is very limited. In this context, I intend to describe and analyse how people spend their money, which are their priorities of consumption, which is the motivation for this behavior of consumption, and which is the perception of self-behavior compared to the self- defined rationality of consumption, or to what extent the situational constraints limit this rationality of consumption.